Design a high performance absorber to improve an anechoic chamber performance - Chai, C.H (Universiti Malaysia Sarawak, UNIMAS, 2010)
This project presents the design of low cost, reliable and good performance microwave absorber for application in anechoic chamber. The absorber is designed to be functioning at frequency range from 3GHz to 15GHz. Different methods were investigated in term of signal absorption of the absorber. The absorbers are made from polystyrene, which were cut into pyramidal shape. The absorber is coated with charcoal mixed with water based paint where it can increase the absorption capability of the absorber. Before the real absorbers are fabricated, the absorber is first designed and simulated using Computer Simulation Technology software to monitor their performances. The measurement of the pyramidal absorber was done to determine its performance. Lastly, the results are compared with commercialized absorber available in the Antenna’s Laboratory of Faculty of Engineering, UNIMAS. The absorber that has been developed is called low cost absorber. The major feature of the anechoic chamber absorber in this project is high absorptions rate of microwave signal and easy to be fabricated using low cost materials.